Pro Design Patterns in Swift - Freeman, Adam, ....- (Berkeley : Apress, 2015)
The Swift programming language has transformed the world of iOS development and started a new age of modern development. Pro Design Patterns in Swift shows you how to harness the power and flexibility of Swift to apply the most important and enduring design patterns to your applications, taking your development projects to master level. This book will teach you those design patterns that have always been present at some level in your code, but may not have been recognized, acknowledged, or fully utilized. Implementation of specific pattern approaches will prove their value to any Swift developer. Best-selling author Adam Freeman explains how to get the most from design patterns. He starts with the nuts-and-bolts and shows you everything through to advanced features, going in-depth to give you the knowledge you need. Pro Design Patterns in Swift brings design patterns to life and shows you how to bring structure and scale to your Swift code with a practical, no-nonsense approach.
Keywords: Computer Science; Computer science; Programming Languages, Compilers, Interpreters